2013
DOI: 10.1111/1460-6984.12044
|View full text |Cite
|
Sign up to set email alerts
|

Story retelling by bilingual children with language impairments and typically developing controls

Abstract: Background To date, there is limited information documenting growth patterns in the narratives of bilingual children with and without primary language impairment (PLI). Aims This study was designed to determine whether bilingual children with and without PLI present similar gains from kindergarten to first grade in the macro- and microstructure of stories told in Spanish and English. Methods and Procedures In this longitudinal study, 21 bilingual children identified with PLI were each matched to a bilingua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
142
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(158 citation statements)
references
References 41 publications
9
142
1
6
Order By: Relevance
“…Squires et al (2014) examined narratives from Spanish-English bilingual children with and without PLI in kindergarten and again in first grade. At each grade level, bilingual children with PLI scored lower than their peers with typical development in each language on measures of narrative micro-and macrostructure.…”
Section: Brief Overview Of the Pli Profile For School-age Bilingual Cmentioning
confidence: 99%
“…Squires et al (2014) examined narratives from Spanish-English bilingual children with and without PLI in kindergarten and again in first grade. At each grade level, bilingual children with PLI scored lower than their peers with typical development in each language on measures of narrative micro-and macrostructure.…”
Section: Brief Overview Of the Pli Profile For School-age Bilingual Cmentioning
confidence: 99%
“…Previous cross-sectional and longitudinal studies on the English narratives of Spanish-English bilingual children have demonstrated that both microstructure and macrostructure improve as children progress from preschool to the early school-age years (e.g., Muñoz, Gillam, Peña, & Gulley-Faehnle, 2003;Rojas & Iglesias, 2013;Squires et al, 2014;Uccelli & Páez, 2007). However, the factors that may support narrative development have not been widely investigated.…”
Section: Narrative Assessment In Young Children: Microstructure and Mmentioning
confidence: 99%
“…Most important, future studies should directly measure whether home literacy activities are completed in English and/or Spanish and whether the language of the activity differentially supports children's English microstructure and macrostructure narrative development. Although there is general consensus that macrostructure is a skill that can transfer between languages (e.g., Pearson, 2002;Squires et al, 2014), at present there is a paucity of research that examines whether direct exposure to narratives in one language at home will transfer to children's macrostructure abilities in the other language. Future studies should also address the frequency of storytelling activities needed to affect growth in narrative abilities.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…As with earlier studies of children's narratives (Bedore et al, 2010;Squires et al, 2014), the parameters employed for the description of children's speech included: speech rate (in number of words per minute); total vocabulary produced (the total number of words in the narrative); number of distinct lexical items; number of verbs and nouns; number of utterances; the longest utterance (in number of words); mean length of utterance (in word count); number of complex and compound sentences, and number of phonological, lexical and grammatical errors.…”
Section: Language Proficiency Assessmentmentioning
confidence: 76%
“…Picture book narratives are commonly used for assessing bilingual children's speech, since they are easy to set up, pleasing and appropriate for children, and serve as an efficient way to solicit a complex language output that can be evaluated for multiple linguistic features (e.g., Bedore et al, 2010;Squires et al, 2014).…”
Section: Language Proficiency Assessmentmentioning
confidence: 99%